Demand for Endodontic Treatment and its Impact on Quality of Life - Bruna Scarlot Avancini; Lorrayne Cesario Maria; Wellen Gobi Botacin; Pamela Barbosa dos Santos; Maria Helena Monteiro de Barros Miotto (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To analyze the impact on quality of life-related to the need for endodontic treatment and possible association with sociodemographic variables. Material and Methods: It was carried out through the application of a sociodemographic script and the Oral Health Impact Profile (OHIP-14). The association between variables was verified using Fisher's exact test and the strength of the association between the independent variables and the impact on quality of life was calculated using the odds ratio (OR). Results: The impact on quality of life was declared by 87.8% of the participants, with physical pain (67.3%) and psychological discomfort (76%) being the most impacted domains. In terms of education level, participants who completed high school or more reported an 88.4% impact on the disability dimension, with around 2.4 times greater chances of suffering impact on this dimension. Individuals living alone reported a greater impact on the psychological disability dimension (54.8%). Participants with limited or no access to dental services, especially through the Unified Health System (NHS), reported a greater impact on the psychological disability dimension (61%). Conclusion: The need for endodontic treatment has a significant impact on quality of life, as stated by 87.8% of the participants, especially in the psychological discomfort (76%) and physical pain (67.3%) domains. These findings were associated with the following sociodemographic variables: gender, race/color, marital status, schooling, socioeconomic status and type of access to oral health services.